Enhancing sustainability in LNG carriers through integrated alternative propulsion systems with Flettner rotor assistance - Nader R. Ammar; Ibrahim S. Seddiek (Brodogradnja)
The maritime industry is actively seeking sustainable solutions to reduce ship emissions and enhance energy efficiency. This study explores the use of alternative fuels and renewable energy sources, focusing on the potential environmental and economic benefits of combining natural gas (NG) fuel with Flettner rotor (FR) technology. The research employs technical, environmental, and economic models to evaluate various scenarios integrating NG fuel with FR in alternative propulsion systems. It investigates three propulsion configurations for LNG vessels: diesel engine (DE-FR), dual fuel diesel engine (DFE-FR), and combined gas and steam turbine engines (COGAS-FR). Results indicate that utilizing six Flettner rotors produces 1.254 MW, resulting in fuel savings of 3.49% to 4.49%, along with notable emission reductions. The COGAS-FR system emerges as the most environmentally friendly option, enhancing energy efficiency by 4.68% based on current ship standards. From an economic perspective, transitioning to the DFE-FR system is identified as an optimal eco-friendly choice, leading to a 9.85% reduction in the levelized energy cost compared to DE-FR. However, it is noteworthy that the COGAS-FR system has the most significant environmental impact, with a cost-effectiveness of $10,954.6 per ton.